Pengaruh Penerapan E-Samsat dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor (Kantor Samsat Makassar II) - Apprilia Apprilia; Desi Linggi Allo; Mika Mallisa; Yohanis Tasik Allo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to determine, firstly, the influence of implementing the e-Samsat system on motor vehicle taxpayer compliance, secondly the influence of tax sanctions on motor vehicle taxpayer compliance, thirdly the influence of implementing e-Samsat and tax sanctions on motor vehicle taxpayer compliance. Data collection techniques used questionnaires and documentation. The number of samples in this study was 93 respondents. The data analysis method uses the classic assumption test and t test. The research results show that there is an influence between e-Samsat and tax sanctions on the level of motor vehicle taxpayer compliance